Oil and gas safety laws in Western Australia - Brown, Kevin (Curtin Business School, School of Business Law, 2006)
This paper explains the source and general principles of the occupational safety and health legislation that applies to the oil and gas industry in Western Australia. It considers the federal legislation known as the Offshore Petroleum Act 2006 (Cth) which replaces the Petroleum (Submerged Lands) Act 1967 (Cth). It also considers the Petroleum Pipelines Act 1969 (WA), the Petroleum (Submerged Lands) Act 1982 (WA), and the Petroleum Act 1997 (WA). This legislation is considered from the point of view of determining which legislation applies to which location; identifying the main provisions of each of those Acts that is concerned with occupational safety and health; and explaining which government department administers each of those Acts.